Paramedic’s Trust and Compliances during COVID-19 Preparedness and Recovery Time - Wasisto, Aryo (Political Science Program, Universitas Negeri Semarang, 2022)
High trust in government’s capability is the key to public compliance in supporting COVID-19 management. The paramedic is a profession that has received attention during times of pandemics because they are on duty as frontlines with a high risk of transmission. This research analyzed a survey of 328 paramedics living in Jakarta to examine their perceptions of the COVID-19 pandemic, the government's readiness, the picture of their psychological condition, their trust in the government, and their belief in themselves in health services. The survey was conducted one week after WHO declared COVID-19 a pandemic. This descriptive study indicates that most respondents have serious concerns about the transmission of the virus. On the side, they are obliged by an oath of service, which demands that they are always ready to serve. Only 30% believe the government can handle COVID-19. All respondents strongly supported the